2002
DOI: 10.1177/014556130208100116
|View full text |Cite
|
Sign up to set email alerts
|

Technique and Timing for Closed Reduction of Isolated Nasal Fractures: A Retrospective Study

Abstract: Isolat ed F ac tures of tile nasal pyramid are am ong tile 1II0St common facia l inju ries. Nevertheless, studies of therapeutic result s fo lio I ving closed reducti on of nasal Factures are rare. \Ve conducted a retrospective clinical relliew of 187 patients who were evaluated for nasal tra uma (including nond islocated [ ractures, dislocated fractures, and contusio ns) at our oto laryngo logy departtneut dur ing 1997 a1/l11998. Ofthis gro up, 96 fract ures lI'ere treated with closed reduction-either under l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 19 publications
(1 reference statement)
0
63
2
Order By: Relevance
“…Most surgeons consider septoplasty only if the initial results of closed reduction are unsatisfactory and the patient continues to complain of nasal obstruction. 7,8 However, closed reduction may not properly address the nasal obstruction caused by a septal fracture. Hung et al found that 18% of patients needed further surgery after closed reduction in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Most surgeons consider septoplasty only if the initial results of closed reduction are unsatisfactory and the patient continues to complain of nasal obstruction. 7,8 However, closed reduction may not properly address the nasal obstruction caused by a septal fracture. Hung et al found that 18% of patients needed further surgery after closed reduction in their study.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very few reports evaluating the long-term results of pediatric nasal bone fractures, and no reports on the link between time to surgery and surgical outcome in a pediatric population [17][18][19]. A pediatric nasal bone fracture is believed to require earlier reduction than in adults, typically within 3-7 days [6][7][8][9]. However, no relevant studies have been performed to show that a delayed reduction could bring unsuccessful surgical results based on long-term follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric patients, however, have been known to need reduction sooner, typically 3-7 days after injury, because later reduction could be challenging [6][7][8][9]. In addition, in pediatric patients with a nasal bone fracture, the septoplasty should be carefully performed to avoid injury to the growth center at the nasal spine of the maxilla, which is very important for future facial growth and development [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard treatment for a nasal fracture is a closed reduction conventionally within 7 days for children and 10 days for adults [6][7][8][9]. This method, although simple, fails to address the deformities of the cartilaginous framework and the nasal septum caused by the injury.…”
Section: Discussionmentioning
confidence: 99%